2022
DOI: 10.1186/s12916-022-02389-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations of handgrip strength with morbidity and all-cause mortality of cardiometabolic multimorbidity

Abstract: Background Cardiometabolic multimorbidity (CM) is an increasing public health and clinical concern. However, predictors for the development and prognosis of CM are poorly understood. The aims of this study were to investigate the relation between handgrip strength (HGS) and the risk of CM and to examine the association of HGS with all-cause mortality risk among patients with CM. Methods This prospective cohort study involved 493,774 participants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 60 publications
(51 reference statements)
0
20
0
1
Order By: Relevance
“…In growing number of studies in children, adults, and elderly, physical strength is considered as a marker of individual developmental processes and health status. It is commonly used to define human body functional capabilities, that is, cardiorespiratory and functional fitness, risks of disability, morbidity, and mortality (Lu et al, 2022; Wang et al, 2020). Physical strength is usually measured by handgrip strength (HGS).…”
Section: Introductionmentioning
confidence: 99%
“…In growing number of studies in children, adults, and elderly, physical strength is considered as a marker of individual developmental processes and health status. It is commonly used to define human body functional capabilities, that is, cardiorespiratory and functional fitness, risks of disability, morbidity, and mortality (Lu et al, 2022; Wang et al, 2020). Physical strength is usually measured by handgrip strength (HGS).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is partly consistent with previously reported results. Specifically, previous studies have reported that low HGS is linked to an increased risk of all-cause mortality, 18,19,28,29 and the coexistence of low HGS and HGS asymmetry in older adults often indicates the presence of severe muscular dysfunction, rather than low HGS or HGS asymmetry seen individually, increasing the risk of adverse health outcomes in older adults. 7,11,30 But another study reported that females rather than males with HGS asymmetry had shorter time-to-death intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros resultados son consistentes con evidencias previas que identifican a la fuerza prensil como un indicador de la composición corporal, específicamente en las variables de masa musculoesquelética y proteínas 23, 24 . Aunque la fuerza prensil evalúa directamente la fuerza máxima de la mano, es un predictor adecuado de la fuerza muscular total en niños, adolescentes, adultos y personas mayores 25 . Particularmente, en población escolar, un estudio de cohorte desarrollado en Australia demostró que la fuerza muscular se encuentra asociada con mayor masa musculoesquelética, debido a mecanismos que involucran hormonas como la testosterona, estrógenos y el factor de crecimiento insulínico tipo 1 (Insulin-like growth factor I, IGF-1, por sus siglas en inglés) en la unión músculo hueso 26 .…”
Section: Discussionunclassified